2009
DOI: 10.1111/j.1749-6632.2009.04766.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lateralization of Metrical Accenting in Musicians

Abstract: The perception of meter, or the alternation of strong and weak beats, was assessed in musically trained listeners through magnetoencephalography. Metrical accents were examined with no temporal disruption of the serial grouping of tones. Results showed an effect of metrical processing among identical standard tones in the left hemisphere, with larger responses on strong than on weak beats. Moreover, processing of occasional increases in intensity (phenomenal accents) varied as a function of metrical position i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
(25 reference statements)
0
22
0
Order By: Relevance
“…Abecasis, Brochard, del Rio, Dufour, and Ortiz (2009) found larger left-hemisphere responses to metrically accented than to metrically unaccented, physically identical tones in a rhythm. At the same time, however, they found that deviants, which were louder than other notes in that study, elicited an increased left-hemisphere response in metrically unaccented positions but elicited a decreased response in metrically accented positions, which suggests that metrically accented notes were expected to be louder, but were not heard as louder.…”
Section: The Present Studymentioning
confidence: 76%
See 2 more Smart Citations
“…Abecasis, Brochard, del Rio, Dufour, and Ortiz (2009) found larger left-hemisphere responses to metrically accented than to metrically unaccented, physically identical tones in a rhythm. At the same time, however, they found that deviants, which were louder than other notes in that study, elicited an increased left-hemisphere response in metrically unaccented positions but elicited a decreased response in metrically accented positions, which suggests that metrically accented notes were expected to be louder, but were not heard as louder.…”
Section: The Present Studymentioning
confidence: 76%
“…Thus, it seems that metrical accents do not create illusory phenomenal accents, which answers the question posed in the title. The intriguing MEG results of Abecasis et al (2009) andIversen et al (2009) may represent some internal process concomitant with metrical accents (most likely motor imagery), a process that does not interact directly with auditory perception. The results of Phillips-Silver and Trainor (2005, 2007, too, need not (and probably should not) be interpreted as implying that rhythms accompanied by head movement or vestibular stimulation are perceived as containing illusory phenomenal accents.…”
Section: Metrical Structure and Auditory Perceptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most investigations of the neural correlates of rhythm processing have used simple stimuli such as tone sequences and compared evoked responses to stimuli in strong and weak metrical positions. Studies of simple stimuli have found that strong metrical percepts are associated with larger evoked potentials and higher-amplitude evoked and induced beta and gamma oscillations (Schaefer, Vlek, & Desain, 2011;Vlek, Gielen, Farquhar, & Desain, 2011;Fujioka, Zendel, & Ross, 2010;Geiser, Sandmann, Jäncke, & Meyer, 2010;Abecasis, Brochard, del Río, Dufour, & Ortiz, 2009;Iversen, Repp, & Patel, 2009;Ladinig, Honing, Háden, & Winkler, 2009;Potter, Fenwick, Abecasis, & Brochard, 2009;Winkler et al, 2009;Pablos Martin et al, 2007;Abecasis, Brochard, Granot, & Drake, 2005;Snyder & Large, 2005;Brochard, Abecasis, Potter, Ragot, & Drake, 2003). Studies of simple stimuli have also demonstrated neural entrainment to a perceived beat and its harmonics (Nozaradan, Peretz, & Mouraux, 2012;Nozaradan, Peretz, Missal, & Mouraux, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, a louder strong beat is not heard as louder, as both the perception and the decision criterion could be modulated by metrical saliency. Results supporting the PC hypothesis and the illusory phenomenal accents have been demonstrated in deviant detection within the same modality: For example, an increased loudness in an auditory rhythm is more noticeable in metrically weak than in metrically strong positions [12,20], as the former is less expected and yields a greater prediction error, or that the latter induces more illusory phenomenal accent to mask the real loudness increment.…”
Section: Introductionmentioning
confidence: 57%